Recombinant human C1 esterase inhibitor for prophylaxis of hereditary angio-oedema: a phase 2, multicentre, randomised, double-blind, placebo-controlled crossover trial. Issue 10102 (30th September 2017) - Riedl, Marc A; Grivcheva-Panovska, Vesna; Moldovan, Dumitru; Baker, James; Yang, William H; Giannetti, Bruno M; Reshef, Avner; Andrejevic, Sladjana; Lockey, Richard F; Hakl, Roman; Kivity, Shmuel; Harper, Joseph R; et al.
Summary: Background: Hereditary angio-oedema is a recurrent, oedematous disorder caused by deficiency of functional C1 inhibitor. Infusions of plasma-derived C1 esterase inhibitor deter attacks of hereditary angio-oedema, but the prophylactic effect of recombinant human C1 esterase inhibitor has not been rigorously studied. We aimed to assess the efficacy of recombinant human C1 esterase inhibitor for prophylaxis of hereditary angio-oedema. Methods: We conducted this phase 2, multicentre, randomised, double-blind, placebo-controlled crossover trial at ten centres in Canada, the Czech Republic, Israel, Italy, Macedonia, Romania, Serbia, and the USA. We enrolled patients aged 13 years or older with functional C1-inhibitor concentrations of less than 50% of normal and a history of four or more attacks of hereditary angio-oedema per month for at least 3 months before study initiation. Patients were randomly assigned centrally (1:1:1:1:1:1), via an interactive response technology system with fixed allocation, to receive one of six treatment sequences. During each sequence, patients received intravenous recombinant human C1 esterase inhibitor (50 IU/kg; maximum 4200 IU) twice weekly, recombinant human C1 esterase inhibitor once weekly and placebo once weekly, and placebo twice weekly, each for 4 weeks with a 1 week washout period between crossover. All patients, investigators, and study personnel who participated in patient care were masked to group allocation during the study. The primary efficacy endpoint was the number of attacks of hereditary angio-oedema observed in each 4 week treatment period. Attack symptoms were recorded daily. The primary efficacy analysis was done in the intention-to-treat population. Safety was assessed in all patients who received at least one injection of study medication. This study is registered withClinicalTrials.gov, numberNCT02247739 . Findings: Between Dec 29, 2014, and May 3, 2016, we enrolled 35 patients, of whom 32 (91%) underwent randomisation (intention-to-treat population) and 26 (81%) completed the study. The mean number of attacks of hereditary angio-oedema over 4 weeks was significantly reduced with recombinant human C1 esterase inhibitor twice weekly (2·7 attacks [SD 2·4]) and once weekly (4·4 attacks [3·2]) versus placebo (7·2 attacks [3·6]), with mean differences of −4·4 attacks (p<0·0001) and −2·8 attacks (p=0·0004), respectively. We recorded adverse events in ten (34%) of 29 patients given twice-weekly recombinant human C1 esterase inhibitor, 13 (45%) of 29 patients given the once-weekly regimen, and eight (29%) of 28 patients given placebo. Headache (twice-weekly treatment) and nasopharyngitis (once-weekly treatment) were the most common adverse events. Two (7%) adverse events (fatigue and headache) were deemed possibly related to treatment with recombinant human C1 esterase inhibitor, but both resolved without additional treatment. No thrombotic or thromboembolic events, systemic allergic reactions (including anaphylaxis), or neutralising antibodies were reported. Interpretation: Prophylaxis with recombinant human C1 esterase inhibitor provided clinically relevant reductions in frequency of hereditary angio-oedema attacks and was well tolerated. In view of the pharmacokinetic profile of recombinant human C1 esterase inhibitor, our results suggest that efficacy of C1-inhibitor replacement therapy might not be a direct function of plasma trough concentrations of C1 inhibitor. Funding: Pharming Technologies.